2018
DOI: 10.1111/roie.12356
|View full text |Cite
|
Sign up to set email alerts
|

Trade policy preference, childhood sporting experience, and informal school curriculum: An examination of views of the TPP from the viewpoint of behavioral economics

Abstract: We investigated how childhood education and experiences helped to form noncognitive skills and later, trade policy preferences. We used individual-level data with approxi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…For labor-intensive industries that meet the qualifications, key guidance should be given to enable them to obtain direct financings from the securities market, bond market, over-the-counter market, industry guidance funds, and venture capital funds as much as possible. [14][15][16][17][18][19][20][21][22][23][24][25][26] From further perspective, firstly, regulations could promote the reductions of the financing products' prices provided by financial institutions, especially for low-cost (less than 10% annual interest) and long-term (3-5 years) financing products. Secondly, securities could perfect emergency on-lending mechanism and risk compensation mechanism during special period, and intensify the pilot reform of commercial credit loans for labor-intensive industries, etc., to effectively lead them to high-quality development.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…For labor-intensive industries that meet the qualifications, key guidance should be given to enable them to obtain direct financings from the securities market, bond market, over-the-counter market, industry guidance funds, and venture capital funds as much as possible. [14][15][16][17][18][19][20][21][22][23][24][25][26] From further perspective, firstly, regulations could promote the reductions of the financing products' prices provided by financial institutions, especially for low-cost (less than 10% annual interest) and long-term (3-5 years) financing products. Secondly, securities could perfect emergency on-lending mechanism and risk compensation mechanism during special period, and intensify the pilot reform of commercial credit loans for labor-intensive industries, etc., to effectively lead them to high-quality development.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…INTAGE was chosen for their good reputation due to their abundant experience with academic research. In the early stages of the COVID-19 pandemic (13)(14)(15)(16) March 2020), the first wave of queries was conducted to gather 4359 observations. INTAGE recruited participants for the survey from among pre-registered individuals, with a participation rate of 54.7%.…”
Section: Methodsmentioning
confidence: 99%
“…What adult people remember from their childhood is seemingly unrelated to their current behaviours. Various existing works using retrospective surveys found that informal education in primary school and childhood circumstances formed adult preferences and worldviews [8][9][10][11][12][13][14][15]. Lee et al explored the role of hygiene school education in childhood on regular handwashing behaviours during the COVID-19 pandemic [1].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the Nikkei Research Company ( NRC) has experience in academic research on Internet surveys [28]- [30]. Therefore, the NRC was commissioned to conduct a nationally representative web survey throughout Japan on October 25-30th, 2018.…”
Section: First Surveymentioning
confidence: 99%